Utilization of Antenatal Care Services and Pregnancy Outcomes among Mothers in a Hospital of Banke - PC, Saru (Journal of Nursing Education of Nepal, 2024)
Introduction: Antenatal care is essential care package providing to women during pregnancy. Adequate and effective antenatal care service utilization helps in increasing good maternal and newborn outcomes. The objective of the study was to find out the utilization of antenatal care services and pregnancy outcomes among mothers. Methods: A cross-sectional study design was used among 196 mothers attended at postnatal ward in Bheri hospital. Non-probability purposive sampling technique was used to select sample for the study. The data were collected using face to face interview technique by using structured schedule and antenatal record review. The collected data were analyzed by using descriptive statistics (frequency, percentage, mean and standard deviation) and inferential statistics (chi square test). Results: Findings showed that 5.1% of mothers had complete utilization of antenatal care services. More than half (63.8%) had good maternal outcomes (no hypertension, no pre-eclampsia etc.) and 54.1% had good neonatal outcomes (well breathing, APGAR score more than seven within one minute and normal birth weight). There was a statistically significant association of utilization of antenatal care services with respondents’ occupation (p=0.001). There was a statistically significant association between respondents’ occupation and maternal outcomes (p=0.015). There was statistically significant association between respondents’ education and newborn outcomes (p=0.042). Conclusions: The majority of respondents had incomplete utilization of antenatal care services. The majority of respondents have good maternal outcomes, and more than half respondents have good newborn outcomes. Activities to encourage public for utilization of complete antenatal care services by concerned health authorities might increase utilization of antenatal care services.